2003
DOI: 10.1093/nar/gkg310
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Kruppel-like factor 5 (KLF5/IKLF) at the CBP interaction region enhances its transactivation function

Abstract: The Kruppel-like factor 5 (KLF5/IKLF) belongs to the Kruppel family of genes which bind GC-rich DNA elements and activate or repress their target genes in a promoter context and/or cellular environment-dependent manner. In the present study, we used the Gal4 fusion assay system to characterize the mechanism of transactivation by KLF5. We demonstrated that the transactivation function of KLF5 was enhanced by CREB-binding protein (CBP) and blocked by wild-type but not mutant E1A. Over expression of CBP reversed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 65 publications
1
57
0
Order By: Relevance
“…29 Several KLFs were reported to be phosphorylated and their transcriptional activities were changed by the modifications. [30][31][32] We found that when several serines on the KLF9 protein were mutated to alanines, its transcriptional activities detected by luciferase report assay for the PPARg2 promoter were greatly enhanced (unpublished data). However, whether post-translational modifications really happened to endogenous KLF9 in adipogenesis needs to be further investigated.…”
Section: Discussionmentioning
confidence: 92%
“…29 Several KLFs were reported to be phosphorylated and their transcriptional activities were changed by the modifications. [30][31][32] We found that when several serines on the KLF9 protein were mutated to alanines, its transcriptional activities detected by luciferase report assay for the PPARg2 promoter were greatly enhanced (unpublished data). However, whether post-translational modifications really happened to endogenous KLF9 in adipogenesis needs to be further investigated.…”
Section: Discussionmentioning
confidence: 92%
“…Tightly controlled protein regulation is a common feature to many transcription factors critically involved in cell growth control, such as p53 (Haupt et al, 1997), HIF-1a (Huang et al, 1998), c-myc (Salghetti et al, 1999), and E2F (Campanero and Flemington, 1997). In addition, instability of KLF5 protein has been suggested in two previous studies (Zhang and Teng, 2003;Bateman et al, 2004). In this study, we tested if and how KLF5 protein is regulated in epithelial cells.…”
Section: Introductionmentioning
confidence: 93%
“…Other factors also regulate the transcription of KLF5 (Chen et al, 2004). Furthermore, KLF5 undergoes post-translational modifications including phosphorylation (Zhang and Teng, 2003) and acetylation (Miyamoto et al, 2003). Tightly controlled protein regulation is a common feature to many transcription factors critically involved in cell growth control, such as p53 (Haupt et al, 1997), HIF-1a (Huang et al, 1998), c-myc (Salghetti et al, 1999), and E2F (Campanero and Flemington, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Like other Sp/KLF transcription factors, KLF5 binds to GC-rich DNA sequences, such as the Sp1 site, GC box and CACCC box (Sogawa et al, 1993;Kojima et al, 1997;Zhang and Teng, 2003) through three zinc-finger domains. KLF5 has been shown to regulate transcription of a number of genes, such as the platelet-derived growth factor-a (PDGF-a) (Aizawa et al, 2004), CyclinD1 (Bateman et al, 2004), Pim1 (Zhao et al, 2008) and PPARg in different cell models.…”
Section: Introductionmentioning
confidence: 99%